Cost‐effective mitigation strategies to reduce bycatch threats to cetaceans identified using return‐on‐investment analysis. Issue 1 (16th October 2019) - Tulloch, Vivitskaia; Grech, Alana; Jonsen, Ian; Pirotta, Vanessa; Harcourt, Rob
Abstract: Globally, fisheries bycatch threatens the survival of many whale and dolphin species. Strategies for reducing bycatch can be expensive. Management is inclined to prioritize investment in actions that are inexpensive, but these may not be the most effective. We used an economic tool, return‐on‐investment, to identify cost‐effective measures to reduce cetacean bycatch in the trawl, net, and line fisheries of Australia. We examined 3 management actions: spatial closures, acoustic deterrents, and gear modifications. We compared an approach for which the primary goal was to reduce the cost of bycatch reduction to fisheries with an approach that aims solely to protect whale and dolphin species. Based on cost‐effectiveness and at a fine spatial resolution, we identified the management strategies across Australia that most effectively abated dolphin and whale bycatch. Although trawl‐net modifications were the cheapest strategy overall, there were many locations where spatial closures were the most cost‐effective solution, despite their high costs to fisheries, due to their effectiveness in reducing all fisheries interactions. Our method can be used to delineate strategies to reduce bycatch threats to mobile marine species across diverse fisheries at relevant spatial scales to improve conservation outcomes. Abstract : Article impact statement : A cost‐effectiveness approach to mitigate dolphin and whale bycatch is cheaper and provides greater benefits over traditional conservation methods. Abstract : Estrategias Rentables de Migración para Reducir las Amenazas que Presenta la Pesca Accesoria para los Cetáceos Identificadas con Análisis de Rendimiento de Inversión Resumen: Las pesquerías amenazan la supervivencia de muchas especies de ballenas y delfines a nivel mundial. Las estrategias para reducir la pesca accesoria pueden ser costosas. El manejo está inclinado hacia la priorización de la inversión para acciones que no son costosas, pero éstas pueden no ser las más efectivas. Usamos una herramienta económica, el rendimiento de inversión, para identificar medidas rentables que reduzcan la captura accesoria de cetáceos en las pesquerías de arrastre, de red y de sedal en Australia. Examinamos tres acciones de manejo: cierres espaciales, frenos sonoros y modificaciones al equipo de pesca. Comparamos una estrategia cuyo objetivo primario era la reducción del costo de la disminución de la pesca accesoria con las pesquerías que poseen estrategias que buscan solamente proteger a las especies de ballenas y delfines. Con base en la rentabilidad y a una resolución espacial detallada, identificamos las estrategias de manejo en Australia que amainan con mayor eficiencia la pesca accesoria de ballenas y delfines. Aunque la modificación de las redes de arrastre fue la estrategia más rentable de todas, hubo muchas localidades en donde los cierres espaciales fueron la solución más rentable. Esto a pesar del alto costo que representan para las pesquerías debido a su efectividad para reducir todas las interacciones de la pesquería. Nuestro método puede usarse para delinear estrategias que reducen las amenazas de la pesca accesoria para las especies marinas móviles a través de diversas pesquerías a escalas espaciales relevantes para mejorar los resultados de la conservación.